Coping intelligence theory: coping strategies, satisfaction and sales commission. Issue 5 (4th June 2018) - Srivastava, Rajesh V.; Tang, Thomas
Abstract : Purpose: This study aims to develop and test a new formative theory of coping intelligence (CI). It asserts that problem- and emotion-focused coping strategies contribute differently to the overall CI latent construct, which, in turn, relates to three outcome variables – job satisfaction, life satisfaction and sales commission. Design/methodology/approach: The study collected data from multiple sources: survey data from 452 boundary-spanning salespeople and sales commission from a company's personnel record. It then investigated the goodness of fit between the study's theoretical SEM model and empirical data. Findings: Problem-focused coping and emotion-focused coping strategies, respectively, define CI positively and negatively. This, in turn, is related to high levels of job satisfaction, life satisfaction and sales commission. After controlling for gender and sales commission, results remain significant. Commission is related to satisfaction. Gender (male) is negatively related to emotion-focused strategy, but positively related to commission. Males have higher sales commission than females, yet both genders have similar life and job satisfaction. Practical implications: Problem-focused coping contributes to life satisfaction, job satisfaction and sales commission, but emotion-focused coping undermines them. Researchers and policymakers need to develop training programs, promote problem-focused coping strategies and help them improve life satisfaction, job satisfaction and sales commission, for females, in particular. Originality/value: CI is more related to job satisfaction and life satisfaction than to commission. The study's concurrent validity demonstrates that CI improves sales commission (objective data) and employee satisfaction. It pays to improve CI.